Management options in the sudden hearing loss of a diabetic patient - Andreea Rusescu; Viorel Zainea; Oana Ruxandra Iana; Irina Ioniță; George Traian Alexandru Burcea-Dragomiroiu; Dragos Cristian Ștefănescu; Dumitru Cristinel Badiu; Florentina Gherghiceanu; Cătălina Pietroșanu; Corina Silvia Pop; Razvan Hainarosie; Mura Hainarosie (Journal of Mind and Medical Sciences)
The aim of our paper is to highlight the main therapeutic principles and the management options in the case of a diabetic patient who has had a sudden hearing loss. Mainly, the aim is to underline the sudden hearing loss treatment adjustment of the diabetic patient compared to the non-diabetic patient. By understanding the mechanism of sudden hearing loss in a diabetic patient, namely the impact of glycemic variations and their implication on the microvascular structures of the inner ear, we try to underline the treatment principles and management options of the previously mentioned combined pathologies. Thus, it is necessary to adapt the classes of drugs used in the case of sudden sensorineural hearing loss of the diabetic patient in comparison with the non-diabetic patient, in order not to aggravate or complicate the patient’s functional status. Therefore, the treatment will need to be adapted both by classes of medication and by the type of administration used. Adequate control of the progression, treatment and complications of diabetes mellitus ensures optimal treatment management in case of a sudden hearing loss and therefore interferes with the favorable functional hearing outcomes. The role of this paper is not only to state the therapeutic principles in the case of sudden hearing loss in a diabetic patient, but also to analyze the impact on the management of potential local and systemic risk factors.